The Significance of District Plan with Different FAR by Use in the System of FAR Deregulation Measures - Izumi, Hiroto (Urban housing sciences, 1997)
After the introduction of FAR (Floor Area Ratio) regulation in accordance with the zoning, the city planning and building regulation system in Japan has introduced various kind of FAR deregulation measures. The purpose of this paper is to examine the significance of District Plan with Different FAR by Use. The results are as follows; (1) District Plan with Different FAR by Use is an epoch making measure in comparison with the other FAR regulation measures. (2) Therefore, it is widely applied in urban areas around CBD for the purpose of improvement of urban environment.